INTEGRATION OF DIGITAL TECHNOLOGY IN LEARNING IN THE INDUSTRIAL ERA 4.0: STUDY FROM THE LEARNING PERSPECTIVE OF ISLAMIC EDUCATION - Salafudin (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
This research intends to describe the role and underlying concepts of digital technology integration in learning in the 4.0 Industrial Age. The topic of integration is seen through the lens of Islamic Education Learning. The conclusion is that the fundamental premise of integrating digital technology in Islamic Education Learning is that technology does not lead to a lack of conceptual understanding or replace the role of student intuition in the learning process. In contrast, the technology attempts to enhance pupils' conceptual comprehension and strengthen their intuitive learning capacities. It is known that there are three didactic functions of digital technology in Islamic Education Learning, namely: Technology for doing Islamic Education, namely technology that functions as an alternative tool for learning media to carry out Islamic Education activities; Technology for practicing skills, namely technology that functions as a learning environment to hone skills in Islamic education; Technology for developing conceptual understanding, namely digital technology that functions as a learning environment to develop students’ conceptual understanding of certain Islamic Education concepts. This third didactic function is most expected from integrating digital technology into Islamic Education Learning.